Comments on the ECtHR Judgment in Verein KlimaSeniorinnen Schweiz and Others v. Switzerland on 9 April 2024 - Kapelańska-Pręgowska, Julia (Polish Review of International and European Law, 2026)
On 9 April 2024, the European Court of Human Rights (ECtHR) delivered three highly anticipated decisions in climate‑related cases: Verein KlimaSeniorinnen Schweiz and Others v. Switzerland, Carême v. France and Duarte Agostinho and Others v. Portugal and 32 states. The Court declared the latter two applications inadmissible but examined the merits in KlimaSeniorinnen. Unlike earlier environmental cases before the ECtHR, these complaints did not concern discrete sources of pollution; they challenged inadequate state responses to the systemic threat of anthropogenic climate change. In KlimaSeniorinnen the Court relied on its ‘living instrument’ doctrine to interpret the European Convention on Human Rights (ECHR) in light of contemporary challenges. It found that Switzerland’s failure to adopt and implement effective climate‑mitigation and adaptation measures breached its positive obligations under Article 8 (right to respect for private and family life). The judgment clarified the scope of substantive obligations, a demanding test for victim status, and a novel approach to causation and burden of proof. It also distinguished between a reduced margin of appreciation for setting climate goals and a broader margin for choosing means, and emphasised procedural safeguards and democratic participation. This article examines the facts, reasoning and broader implications of KlimaSeniorinnen, critiques aspects of the Court’s approach to victim status and judicial activism, and assesses what the decision means for future strategic climate litigation.